Enhancing demographics and career pathways of the space physics workforce in the US - Bagenal, Fran (Frontiers in Astronomy and Space Sciences, 2023)
We present the demographics data for the space physics workforce which are compared with other space sciences fields. We focus on the early stages of college, and draw some lessons from looking beyond the US. We review some of the studies from the National Academies, extracting some relevant recommendations. Studies of the science, technology, engineering and mathematics (STEM) workforce, the physical sciences profession, and specifically the space sciences show that the “pinch point” where the demographics narrow down is at the high school to college stages. We considered the actions that could be made nationally by federal agencies, locally by an institution or individually to enhance and diversify the career pathway through the space sciences.